The Effect Of Addition CaO Mixed With Spinach Extract Of Speed Moulting, Growth And Crab Bakau Survival (Scylla serrata) - Elyza Megawati; Iskandar Putra; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research was conducted in the village of Canang Kering XX Belawan, North Sumatra Province. The purpose of this study was to determine the effect of adding lime water mixed with spinach extract in feed for survival, growth rate, and accelerating the time of moulting mud crab (Scylla serrata).This research was conducted using Experimental Methods with completely randomized design (CRD), those is 5 treatments and 3 replications. P0 (without giving CaO and extract spinach), P1 (Provision 4 ml of CaO and 30 g of spinach extract), P2 (Provision 4 ml of CaO and 35 g of spinach extract), P3 (Provision 4 ml of CaO and 40 g of spinach extract), P4 (Provision 4 ml of CaO and 45 g of spinach extract).Animal testing used was mud crab (S. serrata) with an average initial weight of ±100 gr / individual. Animal testing used were 60 crabs and maintained in a plastic basket measuring (59 x 37 x 17 )cm3during 60 day. The results shows different feed percentages had a significant effect (P <0.05) on absolute weight growth, feed conversion, livelihood, moulting, but not significantly influence (P> 0.05) on SR mangrove crabs. The results showed that the best treatment for absolute weight growth was in the administration of 4 ml of lime water and 40 g of spinach extract of biomass weight (P3) which was 189.67 g, specific growth rate of 3.27%, Best feed conversion  is 7.55, and an average of 18.66 days molting time with a survival rate of 91.33%, Keywords : Mud crab, limewater,Spinach , Moulting, Growth, Life-long rate